Taxonomical account of the Indian spiny clam shrimps (Crustacea: Branchiopoda: Spinicaudata) from the Smithsonian National Museum of Natural History, USA. - Padhye, Sameer M. (Zootaxa, 2020)
I present taxonomical re-descriptions of two Indian spinicaudatan species deposited at the Smithsonian National Museum of Natural History, USA, emphasizing on a few characters not highlighted in the original descriptions. Specimens collected from South India and deposited in the museum forty years ago were assessed and re-described. The study shows that the Cyzicidae species deposited as Caenestheriella sp. is Ozestheria indica while the Eulimnadia species is the widely distributed Eulimnadia michaeli. Many of the taxonomical characters were variable and did not exactly match the earlier description for both the species. Ozestheria indica could be distinguished from other valid Indian species on the telson characters and its occurrence proximity to the type locality of the species. This species is currently restricted to Peninsular India. Eulimnadia michaeli could be identified based on its characteristic egg surface morphology, though, the inner layers of the egg did vary when compared with the western Indian population. Using museum material, the validated species tally of Indian spiny clam shrimps now stands at 8 while 15 still await re-examination.